Investigating Interpersonal Meaning-Making in Indonesian EFL Learners' Writing: A Systemic Functional Perspective - Yasinda Kania Afsari; Murti Ayu Wijayanti; Dhafid Wahyu Utomo (VELES Voices of English Language Education Society, 2021)
This study presents an investigation of interpersonal meaning-making in students’ writing analytical exposition text. The objectives of this study are to describe the common mood types and to describe modality realization used in the text. Nine texts from 144 texts were collected to analyze. The theories from Systemic Functional Linguistics are adapted as the framework to analyze the clause of the text. The findings of this study showed that students have used mood types which can be seen in the use of subject and finite as mood elements, and the use of predicator, adjunct, and complement as residue. The arrangement of mood element ad residue shows the mood type they used. Regarding to SFL theories, the common mood type in this study is declarative as its function of analytical exposition text to discuss topic critically and deeply from one point of view. The result showed that students have attempted to provide information in the text. In the terms of modality, the median modality has a higher frequency in this text than that of high modality and low modality. It indicates that the students have an effort to position themselves and build the relationship to the reader in the text. Moreover, the zero frequency of low modality shows that the students did not provide opportunities for readers to doubt their position in the text. In conclusion, problem –solving approach as the pedagogical implication is appropriate for students to improve cognitive aspects in terms of communicative skills, so students have been able to create the effective analytical exposition text which is intended to discuss something critically from one point of view.